2017
DOI: 10.1007/s11136-017-1567-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life independently predicts long-term mortality but not vascular events: the Northern Manhattan Study

Abstract: Purpose Cardiovascular disease is a major contributor to morbidity and mortality, and prevention relies on accurate identification of those at risk. Studies of the association between quality of life (QOL) and mortality and vascular events incompletely accounted for depression, cognitive status, social support, and functional status, all of which have an impact on vascular outcomes. We hypothesized that baseline QOL is independently associated with long-term mortality in a large, multi-ethnic urban cohort. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…QoL is a broader concept including several dimensions of life such as material resources, social functioning and social relationships, well-being, happiness, and life satisfaction [9]. Beyond the importance of a good SRH and a high QoL in and of themselves, there is also extensive evidence that SRH and QoL are potent predictors for future morbidity and survival/mortality [1214].…”
Section: Introductionmentioning
confidence: 99%
“…QoL is a broader concept including several dimensions of life such as material resources, social functioning and social relationships, well-being, happiness, and life satisfaction [9]. Beyond the importance of a good SRH and a high QoL in and of themselves, there is also extensive evidence that SRH and QoL are potent predictors for future morbidity and survival/mortality [1214].…”
Section: Introductionmentioning
confidence: 99%
“…The perception of quality of life has been established as an efficient form of predicting cardiovascular events and survival rate in hypertensive patients. 16 The results of the present study showed that some modifiable factors, such as muscle strength, body mass index, educational level and blood pressure influence the quality of life of these patients, and that has not been sufficiently investigated in the literature. Thus, in practical terms, interventions such as physical exercise and nutritional monitoring that promote previous control of these variables may positively affect the quality of life of hypertensive individuals.…”
Section: Perspectivesmentioning
confidence: 64%
“…For example, an improvement in this indicator is associated with greater survival rate in hypertensive patients, while a worse quality of life predicts lower survival rates. 16 In the conceptual model proposed by Wilson and Cleary, 32 several factors influence an individual's quality of life, including physical and social functioning, mental health and general health perception. In this context, the SF-36, which is an instrument that evaluates quality of life, includes eight domains (functional capacity, physical aspects, pain, general health, vitality, social aspects, emotional aspects and mental health) that detail these factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wake of irreversible biophysical damage, improvement of symptom burden may still be possible through non-disease modifying symptom management strategies. [3][4][5][6][7][8][9][10][11][12] Based on our prior work, primary lung-related biophysical symptoms of interest to patients with SSc and connective tissue disease-related interstitial lung disease (CTD-ILDs) are cough, dyspnea, exercise tolerance, and fatigue. In these studies, patients voiced an inability to discern whether fatigue was predominantly influenced by underlying ILD or the primary CTD itself.…”
Section: Symptomatology Of Interest To Measure In Ssc-ildmentioning
confidence: 99%